Rare cystic lesion of pancreas : A case report - Shrestha, Bibek; Khatiwoda, Sagar; Bhujel, Sushim; Belbase, Narayan Prasad; Timilsina, Binaya; Shrestha, Nischal; Ojha, Khagendra; Gupta, Ravi (Journal of Gandaki Medical College-Nepal, 2023)
Hydatid disease also known as Hydatidosis or echinococcosis, the cause of which is the larval stage of Echinococcus granulosus. Pancreatic hydatidosis is very rare, with an incidence ranging from 0.14 to 2%. In this report we present a case of 51 years old female patient admitted in our hospital with a cystic lesion in the body of pancreas. Pre-operative computed tomography findings were suggestive of mucinous cystademona for which radical antegrade modular pancreatosplenectomy procedure was done.